Beneficiaries with enhanced resilience to climate risks: Spillover from Agri- SME Partnerships - Mahama, Obed Kwaku (2025)
The impact of climate change remains substantial, and addressing it requires enhanced collaborative efforts. Through the promotion and enhancement of access to CIS-CSA, there is a demand for CIS-CSA created to help improve farmers’ resilience. Public and Private Partnerships, thus the Agri-SMEs lead Accelerator Consortia, were established to sustainably meet the demand created, and in this effort 858,686 farmers have gained direct or indirect access to CIS-CSA innovation, which is improving their resilience to climate change.